(untitled) (Journal of Health, Population and Nutrition, 2012)
In developing countries, malnutrition among children is a major public-health issue. The aim of the study was to describe perceptions of Malawian nurses about nursing interventions for malnourished children and their parents. A qualitative method was used. Data were collected and analyzed according to the phenomenographic research approach. Twelve interviews were performed with 12 nurses at a rural hospital in northern Malawi, Southeast Africa. Through the analysis, two major concepts, comprising four categories of description, emerged: managing malnutrition today and promotion of a favourable nutritional status. The categories of description involved identification and treatment of malnutrition, education during treatment, education during prevention, and assurance of food security. The participating nurses perceived education to be the most important intervention, incorporated in all areas of prevention and treatment of malnutrition. Identification and treatment of malnutrition, education during treatment, education to prevent malnutrition, and assurance of food security were regarded as the most important areas of intervention. DOI: http://dx.doi.org/10.3329/jhpn.v29i6.9898 JHPN 2011; 29(6): 612-618